2011
DOI: 10.1111/j.1475-679x.2010.00394.x
|View full text |Cite|
|
Sign up to set email alerts
|

Who Believes the Hype? An Experimental Examination of How Language Affects Investor Judgments

Abstract: This paper investigates the effect of vivid language on investor judgments. Recent research finds that investor judgments are significantly influenced by disclosure tone (positive versus negative). Holding tone constant, we investigate investors’ reactions to vivid versus pallid information. Drawing on theories from psychology, we predict that investors will be sensitive to the differences between vivid and pallid language when the underlying information is preference inconsistent, but not when the information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(56 citation statements)
references
References 46 publications
2
52
1
1
Order By: Relevance
“…Prior research also finds that trading activity around analyst reports (De Franco, Hope, Vyas, & Zhou, 2014) and annual reports (Miller, 2010) increase with their readability. Consistent with this, Hales et al (2011) note that "although we often think of financial reporting in terms of numbers, language is, in fact, the medium through which companies communicate much of the information on their past and projected future performance." This research suggests that the language used in financial reporting is likely to be an important factor for investors.…”
Section: Importance Of Using a Common Language For Financial Statemenmentioning
confidence: 81%
See 1 more Smart Citation
“…Prior research also finds that trading activity around analyst reports (De Franco, Hope, Vyas, & Zhou, 2014) and annual reports (Miller, 2010) increase with their readability. Consistent with this, Hales et al (2011) note that "although we often think of financial reporting in terms of numbers, language is, in fact, the medium through which companies communicate much of the information on their past and projected future performance." This research suggests that the language used in financial reporting is likely to be an important factor for investors.…”
Section: Importance Of Using a Common Language For Financial Statemenmentioning
confidence: 81%
“…For example, research has shown that language complexity (Miller, 2010), the vividness of language (Hales, Kuang, & Venkataraman, 2011), tone, and readability (Lundholm, Rogo, & Zhang, 2014;Tan, Ying Wang, & Zhou, 2014) affect trading activity and investors' decisions. Our article contributes to this stream of research by demonstrating the importance of the language (English or local) used in annual reports with respect to foreign investment and stock liquidity.…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental investigation of stylistic characteristics is relatively scarce in the recent accounting literature. One exception is Hales, Kuang, and Venkataraman [2011], which investigates the effects of vivid versus pallid language, above and beyond actual information content. Other recent work has looked at the determinants of the style characteristics of verbal communications (Hobson, Mayew, and Venkatachalam [2012]), as well as reactions to verbal communications (Elliott, Hodge, and Sedor [2012], Mayew and Venkatachalam [2012]).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments are well suited to studying disclosure style, but research in the area is relatively sparse. At least one exception is Hales, Kuang, and Venkataraman [2011], which uses an experiment to investigate the effects of vivid versus pallid language, above and beyond actual information content. Future experimental research could provide additional evidence to complement the archival literature by investigating how specific stylistic choices affect investors' judgments, and how managers make stylistic choices in the first place.…”
Section: Introductionmentioning
confidence: 99%
“…This has been a growing area of research interest in the accounting literature since Core's (2001) call for greater use of techniques from computational linguistics to capture large-sample measures of disclosure quality. Recent studies in the accounting and finance literatures have examined investors' reactions to disclosure language as it varies in a variety of characteristics, including optimistic versus pessimistic tone (Henry 2008;Kothari et al 2009;Feldman et al 2010;Demers and Vega 2011;Davis et al , 2014Davis and Tama-Sweet 2012), vividness (Hales et al 2011), and readability (Li 2008;You and Zhang 2009;Miller 2010;Rennekamp 2012;Lawrence 2013;Tan et al 2013;Lundholm et al 2014). Our study extends this literature by examining whether the concreteness of disclosures may also influence investors' judgments and decisions.…”
mentioning
confidence: 99%